Retroviral spread by induction of virological synapses. - Jolly, C; Sattentau, Q (2004)
Cells of the immune system communicate via the formation of receptor-containing adhesive junctions termed immunological synapses. Recently, retroviruses have been shown to subvert this process in order to pass directly from infected to uninfected immune cells. Such cell-cell viral dissemination appears to function by triggering existing cellular pathways involved in antigen presentation and T-cell communication. This mode of viral spread has important consequences for both the virus and the host cells in terms of viral pathogenesis and viral resistance to immune and therapeutic intervention. This review summarises the current knowledge concerning virological synapses induced by retroviruses.